Imperialism and biblical prophecy, 750-500 BCE - Aberbach, David, 1953- (Routledge, 1993)
An exciting, kaleidoscopic presentation of biblical prophecy showing the inextricability of the poetry from the political and military upheavals which occurred at the same time in the ancient Near East.